Figurative Language and Imagery in the Novel Si Anak Cahaya by Tere Liye - Agustina, Lusiana; Supriyanto, Teguh; Setyaningsih, Nas Haryati (Universitas Negeri Semarang, 2023)
This research aimed to (1) find the types and functions of figurative language in the novel Si Anak Cahaya by Tere Liye, (2) find the types and functions of imagery in the novel Si Anak Cahaya by Tere Liye, (3) find the relationship between figurative language forms and imagery in the overall meaning of the novel Si Anak Cahaya by Tere Liye. The research approach was a stylistic approach. Data collection techniques were heuristic technique and note-taking technique. Data analysis techniques were hermeneutic techniques. The research results described (1) The novel Si Anak Cahaya contained figurative language, among others, comparison, metaphor, epic parable, allegory, personification, metonymy, and synecdoche. The dominant figurative language was comparison, totaling 51 data. The functions of figurative language in this novel were clarifying the story, making it easier for readers to understand the story, attracting and entertaining the reader, and elaborating author's intention. (2) The novel Si Anak Cahaya contained images such as vision, auditory, motion, and local color. The dominant image was the motion image, which amounts to 1315 data. The function of imagery in this novel was to clarify the story and make it easier for readers to imagine the story, attract and entertain the reader, and elaborate the author's intention. (3) The relationships between figurative language forms and imagery in this novel aimed to emphasize the title of the novel and the setting of the story relating to the events of 1948 Republic of Indonesia.